2014
DOI: 10.1016/j.vetmic.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of Rhipicephalus sanguineus with Ehrlichia chaffeensis

Abstract: Ehrlichia chaffeensis, the etiologic agent of human monocytic ehrlichiosis, is a tick-borne rickettsial pathogen that is infectious to a wide range of mammals, including dogs and people. Amblyomma americanum, the lone star tick, is considered the primary vector of E. chaffeensis, but this pathogen has been detected in other tick species, including the brown dog tick, Rhipicephalus sanguineus. We hypothesized that the Arkansas strain of E. chaffeensis is infective to R. sanguineus, and used a novel PCR assay to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, D. variabilis , a common human-biting tick, is also present in areas endemic for EMLA , and has been previously shown to acquire other pathogenic Ehrlichia (Kramer et al 1999, de los Santos et al 2007, Pritt et al 2011, Stoffel et al 2014). We have shown that I. scapularis larvae, but probably not D. variabilis larvae, can acquire EMLA by feeding on an infected mouse, and that the bacterium is transmitted transstadially to subsequent life stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, D. variabilis , a common human-biting tick, is also present in areas endemic for EMLA , and has been previously shown to acquire other pathogenic Ehrlichia (Kramer et al 1999, de los Santos et al 2007, Pritt et al 2011, Stoffel et al 2014). We have shown that I. scapularis larvae, but probably not D. variabilis larvae, can acquire EMLA by feeding on an infected mouse, and that the bacterium is transmitted transstadially to subsequent life stages.…”
Section: Discussionmentioning
confidence: 99%
“…In co-feeding transmission, the salivary transfer of agent from an infected vector to a different un-infected vector occurs without a requirement for bacteremia in the host; this has been demonstrated to occur with both Borrelia and Rickettsia (Voordouw 2015). Alternatively, another human biting tick, D. variabilis , is also commonly present in Minnesota and Wisconsin and is a confirmed vector of E. chaffeensis (Stoffel et al 2014), raising the possibility that this species may play a role in the transmission of EMLA.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, E. chaffeensis was not detected in D. albipictus collected from the infected elk described in this report, even though this tick is a member of the same ixodid tribe (i.e. the Rhipicephalinae) as other tick species known to acquire E. chaffeensis under natural and experimental conditions (delos Santos et al, 2007;Roland et al, 1998;Stoffel et al, 2014). Furthermore, the atypical one-host feeding behaviour of D. albipictus means that it is almost certain that these adult-stage ticks fed on the elk, both as larvae and as nymphs.…”
Section: Discussionmentioning
confidence: 62%
“…The first assay was based on a hypothetical outer membrane protein gene (homp) sequence that is unique to the E. chaffeensis genome sequence, which was used to design and optimize a novel fluorogenic real-time PCR assay (Stoffel et al, 2014). This E. chaffeensis-specific assay used the forward primer ECH144762S, reverse primer ECH144994A and the fluorogenic probe ECH144816S (Table 1).…”
Section: Pcr Assays For E Chaffeensismentioning
confidence: 99%
“…2011; Stoffel et al . 2014). Neorickettsia helminthoeca , the agent of salmon poisoning disease, is reported on the American continents and may infect dogs who ingest parasitized salmon (Headley et al .…”
Section: Introductionmentioning
confidence: 99%